Preventive effects of multiple domain interventions on lifestyle and risk factor changes in stroke survivors: Evidence from a two-year randomized trial. Issue 9 (December 2017) - Teuschl, Yvonne; Matz, Karl; Firlinger, Bernadette; Dachenhausen, Alexandra; Tuomilehto, Jaakko; Brainin, Michael; ,
Background and aim: Behavioral and lifestyle interventions in stroke patients need to be intense enough to result in sustainable treatment differences among groups of a randomized trial. Therefore, we report the effects of multidomain interventions on lifestyle and laboratory parameters after 12 and 24 months from a trial that examined whether intensive risk factor management can prevent cognitive decline in ischemic stroke patients. Methods: This prospective randomized, open-label, blinded endpoint trial recruited patients within three months after acute stroke in five Austrian neurological clinics during June 2010 and November 2012. One hundred and one patients were randomized into multidomain intervention and 101 into standard care. Lifestyle interventions were individualized to match predefined targets of regular physical activity, healthy diet, and adequate physiological risk factor control. Results: A total of 167 participants (80 intervention, 87 control) completed the 12-month visit and 155 (76 intervention, 79 control) the 24-month visit. During the first 12 months, adherence to healthy lifestyle and adequately controlled physiological parameters (measured by summary scores) improved significantly in the intervention group compared to controls (p < 0.01). The consumption of reduced-fat milk (p = 0.031), reduced-fat spreads (p = 0.007), and fish (p = 0.021) increased in the intervention group from baseline to 12 months but not in controls. After 24 months, the group difference was significant for the lifestyle summary score but no longer for the combined laboratory lifestyle score. Conclusions: These results demonstrate that intensified individualized multidomain lifestyle interventions in stroke patients are effective in promoting healthy lifestyle in stroke care.